Sleep Habits and Occurrence of Lowback Pain among Craftsmen - Gabriel Omoniyi Ayeni; Oladire Olaniyi; Oluwasegun A Ayeni (Intelektual Pustaka Media Utama, 2014)
Low back pain (LBP) is a leading cause of disability with high economic and public health consequences. The study objective is to determine the association between sleeping habits and occurrence of lowback pain among craftsmen in Owerri. From April to May, 2012, a cross-sectional survey of randomly selected 500 craft workers was done. Data on sociodemographic characteristics and selected lifestyle were collected using an interviewer semi-structured questionnaire. Data analysis was done using descriptive, inferential statistics of chi square and multiple regressions. The findings of multiple regression analyses showed respondents who sleep on soft/saggy surface were almost 5 times more likely to develop LBP independently compared to those with relatively firm/hard surface (OR = 4.56; CI = 2.62 - 7.94; p = 0.001). Craftsmenwith unsteady sleeping posture were twice likely to develop LBP (OR=2.10, CI = 1.04 - 4.25, p<0.001). Longitudinal study is warranted to further explore the relationship between sleep habits and lowback pain.